Monitoring Analysis of the Apron Movement Control Unit for Ground Support Equipment Personnel at the Apron of Husein Sastranegara International Airport, Bandung - Muhamad Ardi Nugraha; Febriansyah Ignas Pradana (CV. Rayyan Dwi Bharata, 2023)
Apron Movement Control (AMC) is an airport personnel who has a license and rating to carry out the duties of being in charge of flight operations, monitoring vehicle traffic, aircraft movement, cleanliness in the airside area, passenger supervision and recording of flight data on the apron. The AMC Unit carries out supervision with the aim of creating work order and safety as well as creating a sense of discipline for airport service users, including discipline for ground handling personnel and GSE officers. The purpose of this research is to find out how the AMC unit supervises Ground Support Equipment (GSE) personnel and to find out what efforts are made by AMC officers in disciplining GSE personnel when they commit violations. This research is a descriptive qualitative research using primary and secondary data. Primary data includes results of observations during research and results of interviews with AMC officers, while secondary data includes Apron Movement Control (AMC) Standard Operation Procedure (SOP) documents. The results of this research can be concluded that the supervision and role of the AMC unit in disciplining GSE officers has been carried out properly and with strict actions in accordance with applicable procedures. This can be proven that almost all work procedures and indicators of work guidelines for the AMC unit have been implemented properly. The AMC unit also gives direct warnings and directions to ground handling officers and GSE officers when they commit a violation. AMC personnel apply sanctions in the form of freezing their driver's license (TIM) or cutting airport passes in the event of a major violation.